Acceptance and adequacy of water supply among flood victims at the temporary evacuation centres in Kuala Krai, Kelantan, Malaysia - Koh, Liew See (Tanjong Malim, 2020)
Acceptance and adequacy of water supply among flood victims at the temporary evacuation centres in Kuala Krai, Kelantan, Malaysia by Koh, Liew See